Rice small C2-domain proteins are phosphorylated by calcium-dependent protein kinase - Kang, C.H., Gyeongsang National University, Jinju, Republic of korea; Moon, B.C., Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; Park, H.C., Gyeongsang National University, Jinju, Republic of korea; Koo, S.C., RDA, Miryang, Republic of korea; Chi, Y.H., Gyeongsang National University, Jinju, Republic of korea; Cheong, Y.H., Sunchon National University, Suncheon, Republic of Korea; Yoon, B.D., Korea Research Institute of Bioscience and Biotechnology, Jeongeup, Republic of Korea; Lee, S.Y., Gyeongsang National University, Jinju, Republic of korea; Kim, C.Y., Korea Research Institute of Bioscience and Biotechnology, Jeongeup, Republic of Korea (Molecules and cells, 2013)
We previously reported that OsERG1 and OsERG3 encode rice small C2-domain proteins with different biochemical properties in Ca2+- and phospholipid-binding assays. Os- ERG1 exhibited Ca2+-dependent phospholipid binding, which was not observed with OsERG3. In the present study, we show that both OsERG1 and OsERG3 proteins exhibit oligomerization properties as determined by native polyacrylamide gel electrophoresis (PAGE) and glutaraldehyde cross-linking experiments. Furthermore, in vitro phosphorylation assays reveal the phosphorylation of OsERG1 and OsERG3 by a rice calcium-dependent protein kinase, OsCDPK5. Our mutation analysis on putative serine phosphorylation sites shows that the first serine (Ser) at position 41 of OsERG1 may be an essential residue for phosphorylation by OsCDPK5. Mutation of Ser41 to alanine (OsERG1S41A) and aspartate (OsERG1S41D) abolishes the ability of OsERG1 to bind phospholipids regardless of the presence or absence of Ca2+ ions. In addition, unlike the OsERG1 wild-type form, the mutant OsERG1 (S41A)::smGFP construct lost the ability to translocate from the cytosol to the plasma membrane in response to calcium ions or fungal elicitor. These results indicate that Ser41 may be essential for the function of OsERG1.